Dyslexia risk gene relates to representation of sound in the auditory brainstem. (April 2017) - Neef, Nicole E.; Müller, Bent; Liebig, Johanna; Schaadt, Gesa; Grigutsch, Maren; Gunter, Thomas C.; Wilcke, Arndt; Kirsten, Holger; Skeide, Michael A.; Kraft, Indra; Kraus, Nina; Emmrich, Frank; et al.
Highlights: Previous studies associate poor reading with unstable speech-evoked brainstem responses. DCDC2 and KIAA0319 risk alleles form a strong genetic link with developmental dyslexia. Genetic burden with KIAA0319 risk is related to unstable speech-evoked brainstem responses. Genetic burden with DCDC2 risk is related to intact speech-evoked brainstem responses. Revealed brain-gene relationships may inform the multifactorial pathophysiology of dyslexia. Abstract: Dyslexia is a reading disorder with strong associations with KIAA0319 and DCDC2 . Both genes play a functional role in spike time precision of neurons. Strikingly, poor readers show an imprecise encoding of fast transients of speech in the auditory brainstem. Whether dyslexia risk genes are related to the quality of sound encoding in the auditory brainstem remains to be investigated. Here, we quantified the response consistency of speech-evoked brainstem responses to the acoustically presented syllable [da] in 159 genotyped, literate and preliterate children. When controlling for age, sex, familial risk and intelligence, partial correlation analyses associated a higher dyslexia risk loading with KIAA0319 with noisier responses. In contrast, a higher risk loading with DCDC2 was associated with a trend towards more stable responses. These results suggest that unstable representation of sound, and thus, reduced neural discrimination ability of stop consonants, occurred in genotypes carrying a higher amount of KIAA0319 risk alleles. Current data provide the first evidence that the dyslexia-associated gene KIAA0319 can alter brainstem responses and impair phoneme processing in the auditory brainstem. This brain-gene relationship provides insight into the complex relationships between phenotype and genotype thereby improving the understanding of the dyslexia-inherent complex multifactorial condition.